Experimental study of flexural behaviour of RC beams strengthened using near surface mounted CFRP strips and ropes. Issue 5 (4th April 2023) - Qaisi, Odai A. L; Ashteyat, Ahmed M.; Murad, Yasmin Z.
Abstract: In this article, an experimental program was carried out to investigate the flexural behaviour of RC beams strengthened using side and bottom near-surface mounted (NSM) CFRP strip and rope. Thirteen reinforced concrete beams (150x250x1600mm) with flexural deficiency were cast. Different configurations have been used for strengthening RC beams, including side NSM, bottom NSM and both of them. Test results have shown that specimens strengthened with NSM CFRP strips have higher load carrying capacity and higher ultimate deflection than that strengthened with NSM CFRP ropes for the same configuration. FRP debonding, concrete cracks and concrete cover separations are more depicted in specimens strengthened with NSM CFRP ropes than that strengthened with NSM CFRP strips. Using NSM CFRP ropes or strips has increased the elastic stiffness of the strengthened specimens. Flexural strengthening of RC beams using CFRP ropes and strips has increased the load-carrying capacity NSM in a range of (18%–51%) and (30%–80%), respectively, compared to the control specimen. It is also found that beams with bottom strengthening increased the flexural capacity by (25%–32%) compared to RC beams with side strengthening